More and Better Jobs in South Asia - Nayar, Reema (World Bank, 2012)
This book is divided into seven chapters. Chapter one is an overview. Chapter two reviews South Asia's recent track record with regard to the quantity and quality of job creation. It traces the relationship of such job creation mostly to overall economic growth and attempts to answer what needs to be done to meet South Asia's employment challenge. Chapter three discusses the key features of labor markets in South Asia, including where the better jobs are, who holds them, and the implications for the employment challenge ahead. Chapter four reviews the business environment constraints affecting, in particular, those firms that have expanded employment and discusses policy options for overcoming the most binding business constraints in South Asia. Chapter five analyzes the dimensions of the education and a skill challenge in the region and discusses policy priorities for improving the quality and skills of graduates of education and training systems. Chapter six reviews the role of labor market policies and institutions in encouraging job creation and protecting workers in the formal and informal economy and discusses possible directions for labor market policies, including options to increase the access of informal sector workers to programs that help them manage labor market shocks and improve their future earnings potential. Finally, chapter seven reviews the key constraints to job creation and the policy priorities for creating more and better jobs in conflict-affected areas.